IMPACT OF CDS ON THE US BOND MARKET - Iguodala, Utomwen S. (2010)
The need to study the impact of credit default swaps on bond markets was borne from a desire to add to the debate which has been raging recently with regards to the role played by credit default swaps in the recent global financial and economic crisis. There have been widespread claims that CDS and the bond market are related and impact on each other. This paper analyses CDS and bond spread for a sample of US firms and finds support for those claims. I evaluate the impact that CDS and some firm specific variables have on bond spreads. Employing time series and panel models, I find that for 21 corporate and financial US firms, CDS and bond spreads are co integrated and CDS has a strong positive effect on bonds. The impact differs across both the corporate and financial issuers. I also find a small positive impact of earnings on spreads for a sample of 20 out of the 21 US firms. There is also strong evidence that during the second part of the global financial crisis, the firms experienced a large shock. This evidence was not present in the initial stage of the crisis.